2004
DOI: 10.1074/jbc.m311192200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a p65 Peptide That Selectively Inhibits NF-κ B Activation Induced by Various Inflammatory Stimuli and Its Role in Down-regulation of NF-κB-mediated Gene Expression and Up-regulation of Apoptosis

Abstract: Because of the critical role of the nuclear transcription factor NF-B in inflammation, viral replication, carcinogenesis, antiapoptosis, invasion, and metastasis, specific inhibitors of this nuclear factor are being sought and tested as treatments. NF-B activation is known to require p65 phosphorylation at serine residues 276, 529, and 536 before it undergoes nuclear translocation. Small protein domains, termed protein transduction domains (PTDs), which are able to penetrate cell membranes can be used to trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
134
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 61 publications
13
134
1
Order By: Relevance
“…Thus, the inhibition of phosphorylated p65 in the nucleus was mainly due to the decrease of nuclear translocation of p65 by treatment with SFN and PEITC in PC-3 C4 cells, and not by the direct inhibition of phosphorylation elicited by SFN and PEITC. Phosphorylation of p65 at serine 529 is known to be required for NF-kB transcriptional activation (Takada et al, 2004b). Since SFN and PEITC could inhibit the basal and UVCinduced NF-kB transcriptional activity, our results suggest that inhibition on NF-kB transcriptional activation by SFN and PEITC is possibly due to the inhibition of nuclear translocation of p65 and consequently phosphorylation of p65 in PC-3 C4 cells.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Thus, the inhibition of phosphorylated p65 in the nucleus was mainly due to the decrease of nuclear translocation of p65 by treatment with SFN and PEITC in PC-3 C4 cells, and not by the direct inhibition of phosphorylation elicited by SFN and PEITC. Phosphorylation of p65 at serine 529 is known to be required for NF-kB transcriptional activation (Takada et al, 2004b). Since SFN and PEITC could inhibit the basal and UVCinduced NF-kB transcriptional activity, our results suggest that inhibition on NF-kB transcriptional activation by SFN and PEITC is possibly due to the inhibition of nuclear translocation of p65 and consequently phosphorylation of p65 in PC-3 C4 cells.…”
Section: Discussionmentioning
confidence: 50%
“…Recent studies have shown that the p65 subunit is directly phosphorylated by an upstream kinase before activating downstream genes (Catley et al, 2004;Takada et al, 2004b). Based on those results, we tested whether SFN and PEITC could also inhibit the nuclear translocation and phosphorylation Effects of SFN and PEITC on IKKa and IKKb activity.…”
Section: Sfn and Peitc Inhibit The Level Of P65 In The Nucleusmentioning
confidence: 99%
See 2 more Smart Citations
“…(17) have been used to deliver peptides and small proteins to cells by an energy-and receptor-independent mechanism with the aim of interfering in signaling processes. Examples include protein transduction domain peptides directed against STAT3 (18), extracellular signal-regulated kinase (19), and NF-B (20). To analyze the importance of the N terminus of MAST205, we synthesized protein transduction domain MAST205 peptides targeting a high scoring PEST sequence, thought to control proteasomal degradation (21) (residues 218 -233; peptide 1) and a potential TRAF2 binding epitope (residues 188 -201; peptide 2).…”
Section: Traf6-induced Nf-b Activity Ismentioning
confidence: 99%